Palynology of the Permian Freshwater Deposit in West Timor - Eko Budi Lelono (Pusat Survei Geologi, 2016)
The Permian sediment is considered to be the oldest formation which occurs in West Timor. It derived from Australian continent which was collided in Late Neogene with the Banda volcanic arc in the Timor Island due to northward moving of this continent. It consists of carbonate (limestone) of Maubise Formation and clastic sediment of Bisane Formation (equivalent to Cribas and Atahoc Formations). This study focusses on the Bisane Formation which lithologically comprises thick calcareous sandstone (0.3 - 5 meters) with abundant marine macrofossils of Chrinoid and common mica. These facts suggest that the Bisane Formation was deposited during Permian age in the shallow marine environment. This interpretation supports the previous study to define shallow marine environment for the Permian sequence. However, this study found different lithology of the Bisane Formation in some locations which is composed of the intercalation of noncalcareous, dark gray to black shale and siltstone showing papery structure and rich of sulphur. Seven shale samples were collected randomly due to outcrop limitation. Stratigraphic range and paleoenvironment of key palynomorphs refer to some authors including Traverse (1988), Brugman et al. (1985), Feng et al. (2008), Jan (2014) and Jha et al. (2014). This paper reveals the result of palynological investigation performed on the noncalcareous black shales of the Bisane Formation. Palynological assemblage characterises Permo - Triassic age as indicated by the existence of striate-bisaccate pollen including Protohaploxypinus samoilovichii, P. fuscus, P. goraiensis, Striatopodocarpidites phaleratus, Pinuspollenites globosaccus and Lunatisporites pellucidus. However, the appearance of trilete-monosaccate spores of Plicatipollenites malabarensis and Cannanoropollis janakii defines that the mentioned shales have an age of Permian. The recovered pollen and spores are associated with the freshwater environment as supported by the disappearance of marine dinoflagellates and noncalcareous lithology. Considering tectonic event during Perm which is marked by rifting, it is possible that the analysed sediment is a product of early syn-rift sedimentation as proved by the occurrence of freshwater deposit (probably lacustrine deposit). If this is the case, the appearance of Permian black shale samples provides opportunity to discover new petroleum system in the Paleozoic sedimentary series of West Timor.Â KEY WORDSPalynology, Permian, Freshwater Sediment, West Timor